Nurses’ perceptions of discharge planning implementation: A descriptive qualitative study - Heryyanoor, Heryyanoor; Diana , Hardiyanti; Melinda Restu , Pertiwi; Asih Dwi, Mulyati (Palembang MediRose Publisher, 2024)
Background: Discharge planning is crucial in hospitals to ensure continuous patient care, thereby preventing re-admissions or complications. However, its implementation still requires improvement due to various obstacles and variances in nurses’ perceptions. Objective: This research aims to explore nurses’ perceptions regarding the implementation of discharge planning. Methods: This study is a descriptive qualitative research involving 14 participants selected through purposive random sampling. Data was collected from April to June 2023 through in-depth interviews, with notes taken and recordings made for transcription. Data analysis was conducted using the Colaizzi method. Results: Participants exhibited a good understanding of discharge planning, yet disparities emerged in their perceptions regarding ten key themes: knowledge, goals, and benefits; organizational aspects in implementation management; activity mechanisms; methods and media employed; implementation steps/flow; implementation content; particularly notable was the theme of implementation timing; evaluation processes in implementation; availability of specialized formats and documentation procedures/format completion; and encountered implementation categories and room-related obstacles. These themes emerged as significant areas needing attention based on the research findings. Conclusion: Nurses’ perceptions regarding the implementation of discharge planning have not been optimized due to constraints imposed by hospital management policies and room management, differences in nurses’ perceptions and attitudes towards implementation, and factors related to patients and their families.